HC-SCR: NOx Reduction using Mn and Cu Catalysts Impregnated in Coconut and Palm Kernel Shell Activated Carbon - Sherra Bellina, Barrabas; Rubiyah, Baini; Norsuzailina, Mohamed Mohamed Sutan; Yakub, Ibrahim; Khairul Anwar, Mohamad Said; Nur Syuhada, Ahmad Zauzi; Noraziah, Abdul Wahab; Hapiszul, Sulaiman (EDP Sciences, 2016)
The characteristics of catalysts impregnated in coconut shell (CS) and palm kernel shell (PKS) activated carbon were determined as potential precursors of catalysts used in a flue gas denitrification system at low temperature. In this study, Manganese (Mn) and Copper (Cu) with metal loading of 8% were impregnated in the activated carbon (AC) before undergoing low temperature calcination process. The morphological properties of samples was analysed using Scanning Electron Microscopy (SEM) and Brunauer, Emmett and Teller (BET) was used to determine the surface area and pore size of samples. The exhaust gas from a diesel engine at a constant flow rate of 4L/min was passed through in a fixed-bed catalytic reactor containing the catalyst, and the concentration of NOx was measured for temperatures ranging from 150°C to 250°C. It was found that the CS catalysts (CS-Mn and CS-Cu) and PKS catalysts (PKS-Mn and PKS-Cu) have the potential to reduce NOx concentration, and results showed that the metal loading of 8% resulted NOx reduction ranging from ~48% to 64%.